2023
DOI: 10.1021/acsomega.2c05984
|View full text |Cite
|
Sign up to set email alerts
|

Strategies To Modify the Surface and Bulk Properties of 3D-Printed Solid Scaffolds for Tissue Engineering Applications

Abstract: 3D printing is one of the effective scaffold fabrication techniques that emerged in the 21st century that has the potential to revolutionize the field of tissue engineering. The solid scaffolds developed by 3D printing are still one of the most sought-after approaches for developing hard-tissue regeneration and repair. However, applications of these solid scaffolds get limited due to their poor surface and bulk properties, which play a significant role in tissue integration, loadbearing, antimicrobial/antifoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…However, the rigidity, plastic deformation limit, and mechanical strength of activated carbon-infused PETG are ∼30% higher than pure PETG samples as measured by their significantly higher Young’s modulus, yield strength, and ultimate strength, respectively (Figure B). The increased mechanical strength of AC-PETG30 samples can be explained by the presence of −CH groups in the FTIR spectra of AC-PETG30 which indicate that the complex carbon chains of activated carbon have been successfully introduced into the PETG polymer matrix . While, in the case of AC-PETG30, due to the higher crystallinity of the compound compared to hydrochar as evidenced by the XRD analysis, a more significant interfacial adhesion between the filler and matrix can occur, which further reinforces the mechanical strength of the composite .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the rigidity, plastic deformation limit, and mechanical strength of activated carbon-infused PETG are ∼30% higher than pure PETG samples as measured by their significantly higher Young’s modulus, yield strength, and ultimate strength, respectively (Figure B). The increased mechanical strength of AC-PETG30 samples can be explained by the presence of −CH groups in the FTIR spectra of AC-PETG30 which indicate that the complex carbon chains of activated carbon have been successfully introduced into the PETG polymer matrix . While, in the case of AC-PETG30, due to the higher crystallinity of the compound compared to hydrochar as evidenced by the XRD analysis, a more significant interfacial adhesion between the filler and matrix can occur, which further reinforces the mechanical strength of the composite .…”
Section: Resultsmentioning
confidence: 94%
“…The increased mechanical strength of AC-PETG30 samples can be explained by the presence of −CH groups in the FTIR spectra of AC-PETG30 which indicate that the complex carbon chains of activated carbon have been successfully introduced into the PETG polymer matrix. 56 While, in the case of AC-PETG30, due to the higher crystallinity of the compound compared to hydrochar as evidenced by the XRD analysis, a more significant interfacial adhesion between the filler and matrix can occur, which further reinforces the mechanical strength of the composite. 57 Finally, the smaller cracks and deformation observed in the SEM images of the AC-PETG30 sample also suggest their higher mechanical strength.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…The 3D printing technique offers an effective way to fabricate scaffolds for tissue engineering, and these 3DP scaffolds are one of the most promising approaches for hardtissue regeneration and repair [63][64][65]. PLA provides desirable characteristics for tissue engineering, but there are limitations stemming from their poor surface properties, bulk properties, hydrophobicity, and lack of recognizable biochemical binding sites, which are necessary for cell-surface interaction [37,63]. To overcome these problems, many efforts have been directed at modifying the surface of the scaffolds, and hydrogels with advanced biomaterial characteristics are one of the solutions [37].…”
Section: Discussionmentioning
confidence: 99%
“…By promoting favorable interactions between cells and the substrate, hydrophilic surfaces play a critical role in enhancing the success of tissue regeneration strategies. Hydrophilicity of scaffolds can be controlled by affected factors such as bulk material, processing method, shape, surface roughness, surface modification, and so forth [200][201][202][203]. For instance, in electrospun nanocomposites of polyhydroxybutyrate/starch/MWCNTs, results showed that MWCNTs had a positive effect on decreasing the fiber diameter and improving the mechanical properties, surface roughness and hydrophilicity.…”
Section: Hydrophilicitymentioning
confidence: 99%